A Pathogenic Relationship of Bronchopulmonary Dysplasia and Retinopathy of Prematurity? A Review of Angiogenic Mediators in Both Diseases - Stark, Ashley; Dammann, Christiane; Nielsen, Heber C.; Volpe, MaryAnn V. (Frontiers in Pediatrics, 2018)
Bronchopulmonary dysplasia (BPD) and retinopathy of prematurity (ROP) are common and significant morbidities of prematurely born infants. These diseases have in common altered and pathologic vascular formation in the face of incomplete organ development. Therefore, it is reasonable to question whether factors affecting angiogenesis could have a joint pathogenic role for both diseases. Inhibition or induced expression of a single angiogenic factor is unlikely to be 100% causative or protective of either of BPD or ROP. It is more likely that interactions of multiple factors leading to disordered angiogenesis are present, increasing the likelihood of common pathways in both diseases. This review explores this possibility by assessing the evidence showing involvement of specific angiogenic factors in the vascular development and maldevelopment in each disease. Theoretical interactions of specific factors mutually contributing to BPD and ROP are proposed and, where possible, a timeline of the proposed relationships between BPD and ROP is developed. It is hoped that future research will be inspired by the theories put forth in this review to enhance the understanding of the pathogenesis in both diseases.